Spatial coding of ordinal information in short- and long-term memory - Ginsburg, Véronique; Gevers, Wim (Frontiers in Human Neuroscience, 2015)
The processing of numerical information induces a spatial response bias: Faster responses to small numbers with the left hand and faster responses to large numbers with the right hand. Most theories agree that long-term representations underlie this so called SNARC effect (Spatial Numerical Association of Response Codes; Dehaene, Bossini, & Giraux, 1993). However, a spatial response bias was also observed with the activation of temporary position-space associations in working memory (ordinal position effect; van Dijck & Fias, 2011). Items belonging to the beginning of a memorized sequence are responded to faster with the left hand side while items at the end of the sequence are responded to faster with the right hand side. The theoretical possibility was put forward that the SNARC effect is an instance of the ordinal position effect, with the empirical consequence that the SNARC effect and the ordinal position effect cannot be observed simultaneously. In two experiments we falsify this claim by demonstrating that the SNARC effect and the ordinal position effect are not mutually exclusive. Consequently, this suggests that the SNARC effect and the ordinal position effect result from the activation of different representations. We conclude that spatial response biases can result from the activation of both pre-existing positions in long-term memory and from temporary space associations in working memory at the same time.